Prevalence of Malocclusion in Western Nepal (Orthodontic Journal of Nepal, 2015)
Introduction: Malocclusion is the improper relationship of maxillary and mandibular teeth. The prevalence of malocclusion varies in different populations of the world.Objective: To study the prevalence of malocclusion in western part of Nepal and to evaluate the gender variation in occurrence of malocclusion.Materials & Method: A total of 1284 subjects were studied. Out of them 656 were male and 628 were female. Intra-oral examination was carried out to assess occlusal types of Class I, II, III according to Angle’s classification of malocclusion, and various occlusal characteristics like crowding, spacing, cross-bite, open-bite and deep bite were recorded. Gender variation in malocclusion characteristics were tested using chi-square test (p